La psicomotricidad en las actividades lúdicas en niños de 4 a 5 años de edad, en el centro de educación inicial “Mario Gerardo Larrea” de la ciudad de Echeandía en el año 2022. - Paredes Mogro, Lesly Mabel (2022)
In this research work carried out at the children’s center “Mario Gerardo Larrea canton of Echeandia in the city of Guaranda, playful strategies are developed to strengthen psychomotricity through educational resources in children aged 4 to 5 years of the above-mentioned children’s centre, corresponding to the elective year MAYO 2022-SEPTIEMBRE 2022. The research was intended to verify whether the teacher uses the playground activities in the classroom to develop skills in the initial level students. To analyse the current problem of methodological strategies that teachers use in the development of psychomotricity in children, it was found that they are scarce, which causes children to be not motivated to perform a task and show little interest in learning. The survey of teachers found that there is a lack of knowledge of techniques that help the proper development of both psychomotricity and playground. It is clear that an activity guide that helps the teacher in their daily planning needs to be implemented urgently. In the face of the problems identified, it is proposed to provide an alternative solution for use in the teachinglearning process, which is to develop a guide to play activities to develop motor skills and strengthen skills in early-level children.